2013
DOI: 10.4314/ijbcs.v7i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the leaf extracts of <i>Moringa oleifera</i> and <i>Jatropha curcas</I> on pathogenic bacteria

Abstract: This study evaluates the antimicrobial activity of the leaf extracts of Moringa oleifera and Jatropha curcas against Staphylococcus aureus and Escherichia coli. Different concentrations of the extracts were subjected to these organisms in which Moringa oleifera showed a higher zone of inhibition on Staphylococcus aureus (2.8 cm) while on E. coli (2.4 cm) while Jatropha curcas showed a higher zone of inhibition on E. coli (2.6 cm) while on S. aureus (1.80 cm). The minimum inhibitory concentration (MIC) of Morin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The decrease in microbial count could be attributed to MOLP being an excellent source of phytochemicals such as flavonoids and phenolic acids, which are used as antimicrobials agents [57]. Moringa oleifera has a strong antimicrobial activity, with this being in line with the work of Okorondu [58], which notes that MO quantitative phytochemical screening showed that it contains alkanoids, flavonoids, cyanogenic glycosides, tannins, and saponins that can be successfully used to reduce and eventually destroy microbes in appropriate dosages. Values expressed as mean ± standard deviation.…”
Section: Microbiological Qualitymentioning
confidence: 87%
“…The decrease in microbial count could be attributed to MOLP being an excellent source of phytochemicals such as flavonoids and phenolic acids, which are used as antimicrobials agents [57]. Moringa oleifera has a strong antimicrobial activity, with this being in line with the work of Okorondu [58], which notes that MO quantitative phytochemical screening showed that it contains alkanoids, flavonoids, cyanogenic glycosides, tannins, and saponins that can be successfully used to reduce and eventually destroy microbes in appropriate dosages. Values expressed as mean ± standard deviation.…”
Section: Microbiological Qualitymentioning
confidence: 87%
“…Visualiza-se na figura 9 que a quantidade de bactérias E. coli foi diminuindo à medida que a concentração do extrato das sementes de moringa foi aumentada, no entanto, atingindo uma maior eficiência a partir de 10% de concentração em volume no efluente não tratado. Okorondu et al (2013) avaliaram a atividade antimicrobiana do extrato foliar de Moringa oleifera sobre Staphylococcus aureus e Escherichia coli. Estes microrganismos foram submetidos a diferentes concentrações dos extratos.…”
unclassified
“…Many studies have explored antimicrobial effects of Moringa leaf powder on waterborne bacteria. The leaf powder of Moringa inhibits E. coli and Staphylococcus aureus (Okorondu et al, 2013). These properties are further shown in its effectiveness in decreasing bacteria when used as a substitute for hand soap (Torondel et al, 2014).…”
Section: Moringa In Water Purificationmentioning
confidence: 99%